Valorisation of wood fly ash on concrete - Teixeira, Elisabete Rodrigues (2019)
Wood fly ash (WFA) is a waste material produced in power plants as result of forest residues combustion to produce power and heat. In countries like Portugal, this waste is disposed of in landfills. Since this material shows pozzolanic characteristics, several studies have been done to evaluate its use as a construction material. This work shows an overview of some published results about the effect of the utilisation of WFA, as a supplementary cementitious material, on the durability and quality of concrete. The results showed that the increase on the wood fly ash content leads to a negative effect on the concrete properties when compared with a conventional concrete. However, the results showed that the behaviour of wood fly ash concrete is very similar to the coal fly ash concrete, which is the most pozzolanic material used in the world. In terms of durability, it was verified that WFA improved the most of the durability characteristics with the exception of carbonation resistance. However, more experimental analysis needs to be developed in terms of wood fly ash concrete durability. Results suggested that using wood fly ash to replace cement is a valuable sustainable option for concrete production. This manuscript discusses the key factors and attempts to provide new information about the application of the wood fly ash on concrete.